DSPTMS320F2812 based variable frequency power inverter - Ahmad Faisal, Hasanuddin (2013)
Nowadays, variable frequency of power inverter is quite used in most application especially on solar power generation A variable-frequency power inverter controls the operating speed of an AC motor by controlling the frequency and voltage of the power supplied to the motor An inverter provides the controlled power based voltage and frequency. Recently, Digital Signal. Processing are used as advanced control technique which confirmed high quality control based on microcontroller and provide additional real time processing throughput in an inverter operation This study investigates the microcontroller of DSPTMS320F2812 based variable frequency power inverter. The DSPTMS320F2812 provides the variable frequency, signal that controls the applied voltage on the gate drive and less harmonics of the frequency at the output of power inverter. From the result, a stable variable frequency power, inverter over frequency range has been obtained and a good agreement has been found between the simulation and hardware of DSPTMS320F2812 based variable frequency power inverter.